“ISLAMIC QUESTION” IN THE CONTEMPORARY PHILOSOPHY OF TRADITIONALISM AND POST-TRADITIONALISM - Юрченко, Е. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The problems of islamization and European identity are observed through the philosophy of traditionalism and posttraditionalism.